Analysis of the concept of Meaningful Learning in light of the Ausubel's Theory - Glenda Agra; Nilton Soares Formiga; Patrícia Simplício de Oliveira; Marta Miriam Lopes Costa; Maria das Graças Melo Fernandes; Maria Miriam Lima da Nóbrega
ABSTRACT Objective: To analyze the concept of Meaningful Learning, according to David Ausubel's Theory. Method: Integrative review using the Meleis's Theoretical Analysis model. Results: The following were identified as antecedents: Previous students' knowledge, potentially meaningful instructional material and student's willingness to learn. The attributes found were: Existence of previous knowledge that allows the connection with the new knowledge; interaction of previous and new knowledge in the cognitive structure; expansion of the cognitive structure through the incorporation of prior knowledge with the new. The consequent ones found: Existence of new knowledge in the cognitive structure of the student, that generate sense and meaning in the cognitive system of the student and that confers importance to him according to the utility for his daily life. Conclusion: The conceptual analysis carried out contributed to the establishment of a more complete definition for Meaningful Learning, which can be appreciated in teaching and research, regardless of the area of activity.